1998
DOI: 10.1007/s007020050069
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease – synergistic effects of glucose deficit, oxidative stress and advanced glycation endproducts

Abstract: Many approaches have been undertaken to understand Alzheimer's disease (AD) but the heterogeneity of the etiologic factors makes it difficult to define the clinically most important factor determining the onset and progression of the disease. However, there is increasing evidence that the previously so-called "secondary factors" such as a disturbed glucose metabolism, oxidative stress and formation of "advanced glycation endproducts" (AGEs) and their interaction in a vicious cycle are also important for the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(136 citation statements)
references
References 104 publications
1
129
0
5
Order By: Relevance
“…A prospective study found that subjects with diabetes mellitus have increased amyloid plaques and neurofibrillary tangles in the hippocampus at autopsy [4], though another post-mortem study did not [40]. In diabetic subjects, accelerated formation of advanced glycation endproducts can cross-link amyloid proteins leading to aggregation into the amyloid plaques Data are given as adjusted differences in hippocampal or amygdalar volume on MRI (ml, 95% CI) per standard deviation (SD) increase in post-load insulin concentration and insulin resistance a Volumes are normalised to average head size [6,41]. In addition, glycation of the microtubule associated protein-tau could lead to formation of neurofibrillary tangles [42].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study found that subjects with diabetes mellitus have increased amyloid plaques and neurofibrillary tangles in the hippocampus at autopsy [4], though another post-mortem study did not [40]. In diabetic subjects, accelerated formation of advanced glycation endproducts can cross-link amyloid proteins leading to aggregation into the amyloid plaques Data are given as adjusted differences in hippocampal or amygdalar volume on MRI (ml, 95% CI) per standard deviation (SD) increase in post-load insulin concentration and insulin resistance a Volumes are normalised to average head size [6,41]. In addition, glycation of the microtubule associated protein-tau could lead to formation of neurofibrillary tangles [42].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of a-lipoic acid on glucose metabolism and energy balance may also play an important role in the functioning of the neurons. Therefore, the importance of a-lipoic acid in the treatment of dementia was proposed as early as 1998 Mü nch et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more and more "nonamyloid" and "non-tau" causes have been proposed, including disturbances in the insulin / insulin receptor glycation, inflammation, oxidative stress and dys-regulation of the cell cycle. Detailed descriptions of these "non-amyloid" and "non-tau" causes have been published in extensive reviews by the group of Peter Riederer and his collaborators (Thome et al 1996;Münch et al 1997;Münch et al 1998;Riederer et al 2006;Arendt et al 2010;). …”
Section: Histopathology Of Alzheimer's Disease -Key To Pathogenesis Amentioning
confidence: 99%